Risk management in Islamic banks: Potentials and challenges - Kamarudin, Awang Mat; Rami Hussein, Salem Althamnah (2019)
This paper addresses a number of the potentials of Islamic banks in managing and avoiding risks, despite many problems and obstacles they experience, which makes them operate in a high-risk and less competitive environment. They operate under regulatory requirements, accounting and regulatory restrictions, in addition to the requirements of Shari'ah compliance and governance. This effort is required to increase efficiency and credibility of the tools adopted for risk management in Islamic financial institutions.